Field evaluation of corrosion mitigation on reinforced concrete in marine exposure conditions. (20th March 2018) - Abd El Fattah, Ahmed; Al-Duais, Ibrahim; Riding, Kyle; Thomas, Michael
Highlights: Corrosion inhibitors decreased steel corrosion rate with cover greater than 25.4 mm. Caltite did not reduce chloride ingress rates. Caltite reduced steel corrosion rate when the cover was greater than 12.7 mm. FA & SC performed better than corrosion inhibitors and SF in reducing chloride ingress. FA & SC performed better than corrosion inhibitors and SF in preventing corrosion. Abstract: The Arabian Gulf is one of the most unfriendly environments for concrete structures due to the harsh chloride attack to reinforcing steel. Durability of concrete is improved by the addition of Supplementary Cementitious Materials (SCMs) and/or chemical agents to concrete mixtures. A marine exposure site was constructed on the west coast of the Gulf in order to study the influence of SCMs and chemical admixtures on corrosion activities in reinforced concrete. Plain and reinforced concrete blocks made from eight mixes, containing cement Type I and Type V with different SCMs and corrosion inhibitors (MCI, CNI, and Caltite), were subjected to natural marine weathering process in exposure zones; tidal, splash and atmospheric for twelve months. Eight blocks, four plain and four reinforced with four black steel bars with various cover depth, were made from each mix. The blocks were monitored and their performance were evaluated in terms of chloride ingress and steel corrosion activity. Corrosion inhibitors showed better effectiveness with cover depth increase. Fly ash and slag cement showed the best performance of corrosion mitigation. Caltite showed marginal reductions in chloride concentrations and a slight improvement in corrosion rates compared to control blocks. The atmospheric-exposed samples showed marginal increase in chloride surface concentration unlike the tidal-exposed ones. The results illustrate the importance of ensuring adequate cover depth for achieving a long service life in harsh environment.